Experienced based learning: physiology from Islamic perspective - Abdul Ghani, Radiah; Ikmal Hisham, Ahmad Irfan (2020)
Teaching and learning in the 21st century is a huge challenge, and every discipline has to cope with all the changes that occur within society. This project aimed to demonstrate how Experienced Based Learning (EBL) can be a valuable option in the process of learning among undergraduate students of BSc Biomedical Science in Physiology and Islamic perspective. This project aimed to answer these research questions: Is using an EBL is more effective in improving student learning than the traditional teaching method. The effectiveness of the teaching methods were measured via: (1) improvement in student learning outcomes, (2) improvement in student motivation in learning the topic, and (3) improvement in the student experience such as student enjoyment, satisfaction, and perceived difficulty in learning the topic. The knowledge gained from this project can be used by science educators to use effective teaching tools to improve knowledge in science through Islamic perspective, which has the potential to increase the number of students well-prepared for entering biomedical science careers.